An Evaluation on Changes of Psychosomatic Status Indexes of Educational Process Subjects Depending on the Type of Manual Intervention - Skrypka Олена; Karvatsky Ігор (Psychosomatic Medicine and General Practice, 2025)
In modern context evaluation of the efficacy of manual therapy as a potential tool of optimization of the psychosomatics is relevant not only for military personnel, but also for subjects of educational process who are locating presently in high-risk area zones and are exposed to chronic emotional tension. In this respect not only changes in mobility under the influence of manual procedures, but also to the dynamics of changes of somatic and mental status merits attention. This publication presents the results of a study involving 30 relatively healthy student volunteers aged 20-25 years. The subjects were divided into three quantitatively equal groups according to the type of manual intervention, namely courses of massage, post-isometric relaxation (PIR) and a combination of massage and PIR courses (each course consisted of 5 sessions). Before and after each session, the indexes of ankle joint dorsal flexion and extension of the ankle joint were evaluated using goniometry, and heart rate (HR) and blood pressure (BP) were measured as well. Before and after each manual therapy course, the subjects were surveyed using a modified mini-Mult version of the MMPI test. The most significant increase of ankle joint mobility, accompanied by a slight increase of HR and BP values, was observed in response to PIR procedure. The least significant increase in ankle joint mobility was observed in response to massage procedure, but with accompanying decrease of HR and BP values. The combined course (massage + PIR) had positive effect upon ankle joint mobility indexes, resulting in decrease of HR and BP indexes, and produced comparatively most optimal changes of psychoemotional state, including a decrease of depression and instability levels, and an increase of communicability level. Considering the differences in pattern and intensity of changes of evaluated indexes induced by different manual procedures, it is reasonable to choose exact manual procedure depending on the intention of the intervention: for maximum joint mobility it would be reasonable to choose PIR; for complete relaxation the massage should be chosen; for psychosomatic state optimisation combined procedures are preferable.